2015
DOI: 10.3109/1354750x.2015.1096305
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 72 (Hsp72) specific induction and temporal stability in urine samples as a reliable biomarker of acute kidney injury (AKI)

Abstract: We demonstrated that urinary heat shock protein of 72 KDa (Hsp72) is a sensitive biomarker for the early detection of acute kidney injury (AKI). However, whether Hsp72 induction during an AKI episode is kidney-specific is unknown, as well as, the degree of Hsp72 stability in urine samples. In rats that underwent bilateral renal ischemia and reperfusion (I/R), Hsp72 levels were evaluated in several tissues and in collected urines under different storage and temperature conditions, as well as in variable numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…In contrast, in the patients treated with eplerenone, the urinary 8-hydroxylated-guanosine levels remained constant throughout the follow-up (Figure 5A), however, no difference between the groups was observed. In accordance with these findings, the percentage change from baseline levels of urinary HSP72 (25)(26)(27) show a trend to increase in the placebo compared with the eplerenone group (33.4618.4% versus 8.563.0%, P=0.12, Figure 5B). No changes were observed in either urinary KIM-1 ( Figure 5C) or serum TGF-b 1 levels ( Figure 5D).…”
Section: Resultssupporting
confidence: 80%
“…In contrast, in the patients treated with eplerenone, the urinary 8-hydroxylated-guanosine levels remained constant throughout the follow-up (Figure 5A), however, no difference between the groups was observed. In accordance with these findings, the percentage change from baseline levels of urinary HSP72 (25)(26)(27) show a trend to increase in the placebo compared with the eplerenone group (33.4618.4% versus 8.563.0%, P=0.12, Figure 5B). No changes were observed in either urinary KIM-1 ( Figure 5C) or serum TGF-b 1 levels ( Figure 5D).…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, HSP72 has been reported as an early and sensitive urinary biomarker of acute kidney injury in several studies . To our knowledge, this is the first study evaluating uHSP72 levels in DN in T2DM patients, in which uHSP72 levels were significantly increased in both micro‐ and macroalbuminuric diabetics compared with normoalbuminuric diabetics and healthy controls, indicating its positive association with disease progression.…”
Section: Discussionmentioning
confidence: 68%
“…The significant positive correlation between IL-1b level and NLRP3 relative expression may explain the fundamental role of NLRP3 in the development of DN via the action of its product, IL-1b, as it has been demonstrated that IL-1b level was significantly increased in patients with DN and positively correlated with renal dysfunction (35,36). Furthermore, HSP72 has been reported as an early and sensitive urinary biomarker of acute kidney injury in several studies (37)(38)(39)(40)(41). To our knowledge, this is the first study evaluating uHSP72 levels in DN in T2DM patients, in which uHSP72 levels were significantly increased in both micro-and macroalbuminuric diabetics compared with normoalbuminuric diabetics and healthy controls, indicating its positive association with disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…Using Western blot technique, urinary HSP72 (Barrera‐Chimal et al, 2011; Morales‐Buenrostro et al, 2014; Ortega‐Trejo et al, 2015; Perez‐Villalva et al, 2017), KIM‐1 (Perez‐Rojas et al, 2007; Vaidya et al, 2005, 2006), and SerpinA3K (Sanchez‐Navarro et al, 2019) levels were detected in the diluted urine (1:10 in 0.9% saline solution) as follows: 10 μl of each dilution was loaded and resolved in 8.5% SDS‐PAGE. A mouse anti‐HSP72 (ENZO Life Sciences, cat.…”
Section: Methodsmentioning
confidence: 99%